Sense, Nonsense, and Violence: Levinas and the Internal Logic of School Shootings. Issue 4 (August 2015) - Keehn, Gabriel; Boyles, Deron
Abstract Utilizing a broadly Levinasian framework, specifically the interplay among his ideas of possession, violence, and negation, Gabriel Keehn and Deron Boyles illustrate how the relatively recent sharp turn toward the hypercorporatized school and the concomitant transition of the student from simple (potential) customer to a type of hybrid consumer/consumable has rendered it more difficult for students to see themselves as engaged in any type of serious ethical relationship with those around them. To be unable to see their peers as Others, in other words, makes it easier for students to perpetrate a specific type of violence against them. Keehn and Boyles suggest that current popular policy responses to gun violence in schools (such as increased security, zero‐tolerance policies, antibullying initiatives, and mental‐health policy revisions) are approaches that, at best, fail to address the root cause of gun violence in schools and, at worst, are themselves branches of that root: namely, a homogenizing corporatism that creates an ethical vacuum in the schoolhouse.